1980
DOI: 10.1063/1.439694
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and structure in aqueous NaNO3 solutions

Abstract: Two concentrated (5 and 7 mol l−1) aqueous solutions of NaNO3 were investigated by x-ray diffraction. The features of the total radial functions calculated from experimental intensity data show that the positional correlation is not very strong in the systems investigated. However, it is possible to account for experimental data only by using models in which hexahydrated Na+ ions have definite correlations with NO3− ions, even if not through formation of isolated ion pairs. The compatibility of our observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 13 publications
10
50
1
Order By: Relevance
“…In almost every case tested, we found that the V0 values corresponded to n, = 4, 6, 8, or 9, as would be anticipated on geometrical grounds. For example, for Nab(aq), we calculate V: , , = 23.7, 6.5, -9.9, -17.9, and -31.2 cm3 mol-' for coordination numbers 4, 5, 6, 7, and 8 respectively; the observed value of -6.6 cm' mol-' is consistent with n, = 6, in agreement with a recent X-ray diffraction study (40). Simi--0 .…”
Section: Theoretical Interpretation Of Absol~lte Molar Volumes Of M2+supporting
confidence: 78%
“…In almost every case tested, we found that the V0 values corresponded to n, = 4, 6, 8, or 9, as would be anticipated on geometrical grounds. For example, for Nab(aq), we calculate V: , , = 23.7, 6.5, -9.9, -17.9, and -31.2 cm3 mol-' for coordination numbers 4, 5, 6, 7, and 8 respectively; the observed value of -6.6 cm' mol-' is consistent with n, = 6, in agreement with a recent X-ray diffraction study (40). Simi--0 .…”
Section: Theoretical Interpretation Of Absol~lte Molar Volumes Of M2+supporting
confidence: 78%
“…20,21 On the other hand, Caminiti et al investigated the hydrated structure of ions in NaNO 3 solution of 5-7 mol dm 23 by using the X-Ray diffraction technique. 22 Their results show the number of water molecules in the first hydrated shell of NO hydration is only 1-3 in their reports, while it is 3-6 even in very concentrated solution. 22 Thus, the calculations above can only provide the foundational theoretical models of hydrated nitrate but can not explain the experimental phenomena quantificationally.…”
Section: Introductionmentioning
confidence: 93%
“…22 Their results show the number of water molecules in the first hydrated shell of NO hydration is only 1-3 in their reports, while it is 3-6 even in very concentrated solution. 22 Thus, the calculations above can only provide the foundational theoretical models of hydrated nitrate but can not explain the experimental phenomena quantificationally. In this article, we optimize the nitrate clusters with 1-6 hydrated water molecules to obtain their geometries, relative energies, binding energies, and vibrational frequencies and compare the results with those in experiments.…”
Section: Introductionmentioning
confidence: 93%
“…Sequential polymerization of ionic pair results in formation of associations having n=2-4. It is to be noted that cluster structure [14], ionic pairs and ionic triplets [11] were experimentally observed in concentrated aqueous solutions of NaNO 3 . At 15-45 °C in KNO 3 solutions hydration degree of contact ion pairs seems to be higher [4]; this might be indirectly proved by empirical compositions of KNO 3 .…”
Section: →Brmentioning
confidence: 98%
“…Pseudocompounds may be represented as hydrated contact ion pairs and their associates, as was done in the case of KNO 3 solutions [4]. This conclusion is proved by computer simulation of ion coordination based on X-ray studies of concentrated aqueous salt solutions [11][12][13]. Figure 5 shows one of the possible sequential changes of composition and structure of nNaNO 3 .…”
Section: →Brmentioning
confidence: 99%